The Corporate Saving Glut and the Current Account in Germany - Thorsten Klug; Tobias Schuler; Eric Mayer (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
We investigate for Germany the positive correlation between the corporate savings glut in the non-financial corporate sector and the current account surplus from a capital account perspective. By employing sign restrictions our findings suggest that mostly labor market, world demand and financial friction shocks can account for the joint dynamics of excess corporate savings and the current account surplus. Private savings shocks, in contrast, cannot explain the correlation. We conclude that a corporate savings glut is a main driver of the current account surplus.
Keywords: E32; F32; F45; 330; Current account; corporate savings; macro shocks